Book Reviews. Issue 1 (1st March 2021) - Unknown
Abstract : Lisa Greenwald, Daughters of 1968: Redefining French Feminism and the Women's Liberation Movement (Lincoln, NE: University of Nebraska Press, 2018). Eric T. Jennings, Escape from Vichy: The Refugee Exodus to the French Caribbean (Cambridge, MA: Harvard University Press, 2018). Kathleen Keller, Colonial Suspects: Suspicion, Imperial Rule, and Colonial Society in Interwar French West Africa (Lincoln, NE: University of Nebraska Press, 2018).